Pharmaceutical Compounds as Photostabilizers. - Al-khateb, Esraa Ismael; Alsamarrai, Khalaf F; Ahmed, Ahmed (Al-Nahrain Journal of Science, 2018)
n this paper, some pharmaceutical compounds were used and their impact on the photostability of polymer poly (vinyl chloride) (PVC) was study. The PVC films containing a variant concentration of compounds 0.25, 0.5, 1% by weight were produced by casting method from tetrahydrofuran (THF) solvent. The photostabilization activities of these compounds were determined by calculating the photodegradation rate constant for photostabilizer (kd). The stabilizing efficiency of pharmaceutical compounds is attributed to the replacement of the labile chlorine atoms on the PVC chains by a relatively more stable moiety of the pharmaceutical stabilizer. The Photostabilization activity of these compounds is determined by weight loss method with irradiation time.